Rifampin‐induced acute kidney injury and hemolysis: A case report and literature review of a rare condition - Fateen Ata (12217764) (2022)
Rifampicin is a bactericidal drug used in various infectious diseases, including tuberculosis (TB). Nephrotoxicity is a rare side effect of intermittent Rifampin use and even less commonly continued use. We report a case of Rifampin‐induced acute tubular necrosis and hemolysis in a patient with latent TB with a relevant literature review. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.6780